Low back pain at presentation in a newly diagnosed diabetic. Issue 6 (1st December 2002) - Ladhani, S; Phillips, S D; Allgrove, J
Abstract : Insulin dependent diabetes mellitus predisposes to a range of different and unusual infections, including epidural and psoas abscesses. However, they occur mainly in adults with longstanding diabetes. We report the case of a 12 year old boy who presented with diabetic ketoacidosis and low back pain, and was subsequently diagnosed with both a left psoas abscess and an extensive thoracolumbar spinal epidural abscess measuring 20 cm in length. This case report highlights the need to maintain a high index of suspicion for epidural abscesses in children presenting with fever and localised back pain. Early diagnosis with appropriate imaging and aggressive management can prevent development of permanent neurological damage as was the case in our patient.